Joint analysis of transcriptional metabolism for flavonoid synthesis during different developmental periods in oil palm exocarp - Zhang, Ruimin; John Martin, Jerome Jeyakumar; Liu, Xiaoyu; Li, Xinyu; Zhou, Lixia; Li, Rui; Fu, Xiaopeng; Li, Wenrao; Cao, Hongxing (Frontiers in Plant Science, 2025)
To identify candidate genes for breeding oil palm varieties with high flavonoid content through molecular biotechnology, this study analyzed the metabolomes and transcriptomes of oil palm exocarp at different developmental stages using LC-MS/MS and RNA-Seq techniques. The green fruiting type (FS) oil palm exocarp at 95 days (FS1), 125 days (FS2), and 185 days (FS3) after pollination served as the materials. The enzyme genes F3H, CHS, ANS, and DFR were positively correlated with Quercetin-3-O-sambubioside. DFR also showed positive correlations with Afzelechin, Epiafzelechin, and Baimaside. In contrast, F3H, CHS, and ANS were negatively correlated with Hesperetin-7-O-glucoside. Additionally, CYP73A, UGT73C6, FG2-1, and FG2-2 were negatively correlated with Afzelechin, Epiafzelechin, Quercetin-3-O-sambubioside, and Baimaside, while CYP75A was negatively correlated with Epiafzelechin, Quercetin-3-O-sambubioside, and Baimaside. These results suggest that F3H, CHS, ANS, and DFR play a role in promoting Quercetin-3-O-sambubioside* synthesis, with DFR further enhancing the production of Afzelechin, Epiafzelechin, and Baimaside. On the other hand, F3H, CHS, and ANS may inhibit Hesperetin-7-O-glucoside synthesis. Meanwhile, CYP73A, UGT73C6, FG2-1, and FG2-2 appear to suppress the synthesis of multiple flavonoids, including Afzelechin, Epiafzelechin, Quercetin-3-O-sambubioside*, and Baimaside. Lastly, CYP75A is implicated in suppressing Epiafzelechin, Quercetin-3-O-sambubioside*, and Baimaside synthesis. These findings provide a foundation for future molecular breeding efforts targeting flavonoid-rich oil palm varieties.